Correlation of antioxidant activity and volatile oil chemical components from Schizonepeta tenuifolia herbs by chemometric methods. (18th December 2017) - Guo, ShuChen; Yu, Sheng; Qian, Yan; Hu, MinHui; Shan, MingQiu; Chen, PeiDong; Chen, YaYun; Zhang, Li; Ding, AnWei; Wu, QiNan; Li, Sam Fong Yau
ABSTRACT: In this paper, 15 batches of volatile oil from Schizonepeta tenuifolia herbs (STVO) originating from different areas of China were used to identify and quantify eight main components by GC-MS and to evaluate the antioxidant activity with 1, 1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging capacity by the HPLC method. The results indicated that with respect to the antioxidant activity and the contents of the main compounds, there were notable differences among the STVOs. IC50 values of the STVOs ranged from 0.016 to 1.518 mg/mL. To determine the correlation of the chemical components and the antioxidant activities, multiple linear regression analysis (MLRA) and partial least square analysis (PLSA) were performed. As a result, (+)-pulegone and (-)-menthone showed much closer relationships than the other components in each analysis. Hence, it was concluded that (+)-pulegone and (-)-menthone were the characteristic components that may exhibit potent antioxidant activities in STVO.